Effects of drought and salt stress on the root phenotype of wheat seedlings and underlying gene expression analysis - Tang, Kaiyue; An, Chuanjing; Li, Lixia; Sun, Tao; Song, Jiancheng; Zhao, Jiqiang (Frontiers in Plant Science, 2024)
In our previous study, three TaPSK genes highly expressed in the roots of wheat were screened. To explore the effects of adverse stress on the wheat root phenotype and the expression of TaPSK3, TaPSK9 and TaPSK10, we measured the phenotypic parameters of the JM22 root system at the seedling stage after treatment with different concentrations of NaCl and PEG6000. The results revealed that drought and salt stress significantly inhibited phenotypic parameters such as total root length, root surface area, root biomass distribution estimation and root tip number in wheat. Notably, salt stress causes wheat roots to germinate more root hairs. Additionally, the relative expression levels of TaPSK3, TaPSK9, and TaPSK10 were analyzed via RT-qPCR within 72 h of treatment with 150 mM NaCl and 30% PEG6000. The results revealed that the expression of TaPSK3 did not change significantly during salt stress but was upregulated approximately five-fold at 12 h of drought stress. The gene expression levels of TaPSK9 and TaPSK10 were upregulated to varying degrees but gradually returned to normal at 72 h. These results show that when wheat is stressed, the expression of TaPSK genes is upregulated to promote root growth and ensure the normal growth and development of plants. This study provides data and theoretical support for further study of TaPSK gene function and cultivation of high-quality wheat plants with strong stress resistance.